2017
DOI: 10.1016/j.jebo.2017.07.031
|View full text |Cite
|
Sign up to set email alerts
|

Capital flows and GDP in emerging economies and the role of global spillovers

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…( 3)In addition, the study assumes no contemporaneous relationship between economic growth and macroeconomic instability, and between inflation rate between international capital inflow especially the FDI following many empirical studies that reported no association between economic growth and inflation rate (See (Bai, 2013;Bailliu, 2000;Batu, 2017;Beckmann & Czudaj, 2017)). That is, neither economic growth nor capital inflow is expected to affect macroeconomic instability.…”
Section: Methodsmentioning
confidence: 99%
“…( 3)In addition, the study assumes no contemporaneous relationship between economic growth and macroeconomic instability, and between inflation rate between international capital inflow especially the FDI following many empirical studies that reported no association between economic growth and inflation rate (See (Bai, 2013;Bailliu, 2000;Batu, 2017;Beckmann & Czudaj, 2017)). That is, neither economic growth nor capital inflow is expected to affect macroeconomic instability.…”
Section: Methodsmentioning
confidence: 99%
“…To examine expectation effects from monetary policy we apply a panel VAR in the tradition of Canova and Ciccarelli (2009) and Beckmann and Czudaj (2017a), which builds on the formulation of the VAR model…”
Section: B Empirical Methodologymentioning
confidence: 99%
“…To examine expectation effects from monetary policy we apply a panel VAR in the tradition of Canova and Ciccarelli () and Beckmann and Czudaj (), which builds on the formulation of the VAR model yit=j=1p1Ditalicit,jYtj+j=1p2Citalicit,jWtj+eit, where i = 1, …, N and t = 1, …, T are the indices for the cross section and the time dimension, respectively. For our VAR model the vector y it of dimension G × 1 is defined as yitalicit=pritFi,t12πi,tFi,t12GDPi,t],,,,πitalicitnormalGDPitaliciti, where pr it denotes the monetary policy rate for country i , π it gives its inflation rate, and GDP it represents its GDP growth rate.…”
Section: Data and Empirical Modelingmentioning
confidence: 99%
See 2 more Smart Citations